Hidden peril [large type] - Hannon, Irene (Hannon, Irene. Code of honor, 2018)
"Set in St. Louis, a fair trade shop owner and a local police detective find themselves in the middle of international intrigue and in the sights of a ruthless killer when people connected with the shop begin turning up dead"--